COMMUNICATION COMPONENT FORMATION OF TEACHERS' COMPETENCE IN THE MENTORING PROCESS - Vera T. Sopegina (Russian State Vocational Pedagogical University, 2016)
The aim of this article is to present the integration process and special pedagogical competence in solving production and pedagogical challenges in the educational organizations and production enterprises engaged in the training of mentors.Methods. The methods involve the analysis of psycho-pedagogical and methodological literature on the issue; analysis of the Federal State Educational Standards and professional standards; modeling of processes.Results and scientific novelty. The problems of formation of communicative competence in the preparation of teachers are considered. The characteristic of the formation levels of mentoring such as «mentor-formal»; «mentor-theoretician», a «mentor-coach»; «mentor-adviser»; «mentor-professional» are given. The pedagogical potential of the phenomenon of «mentoring» is disclosed; an innovative way of mentoring within the competence approach is shown. The integrative activity of the teacher in solving production and pedagogical problems is analysed.Practical significance. The results can be used by trainers and mentors in the formation of communicative competence of students. The implementation of integration model of pedagogical and production tasks will provide the formation of communicative competence as part of vocational training. Using the obtained results can improve the effectiveness of vocational teacher education.